Systematic literature review on the barriers and benefits of Malaysian Green Rating System implementation / Nur Humaira Youszelan and Asniza Hamimi Abdul Tharim - Youszelan, Nur Humaira; Abdul Tharim, Asniza Hamimi (2019)
Malaysian construction industry is one of major industry contributing to the growth of economic. Unfortunately, as a lot of negative impacts on the environment from the construction industry have lead Malaysia to a growing realization that there is a need for more sustainable buildings. Malaysian green rating system being developed to progress and adapt itself to the tropical climate. Though, current sustainable development is facing challenges and barriers which give different perception to the players of the industry. The aim of this paper is to study the barriers and benefits of implementation of Malaysian green rating systems. Thus, this paper analyses the existing literature on the predictors on implementation barriers and benefits. A systematic review was applied to identify the findings and variables to suit the sustainable development in Malaysia context.